PRODUCTIVITY OF SNAKEHEAD FISH (Channa striata) AS A SOURCE OF WOUND HEALING - Destriman Laoli; Eliyunus Waruwu; Betzy Victor Telaumbanua; Ratna Dewi Zebua; Ridho Victory Nazara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Snakehead fish (Channa striata) is a freshwater fish that can be found throughout Indonesian waters. Snakehead fish in today's society has been associated with medicine. Snakehead fish is processed into various types of dishes and then served to sick families, especially for those who are postoperative because its content has been clinically proven in several diseases. Snakehead fish has a high protein content, especially albumin and essential amino acids, fat, especially essential fatty acids, minerals, especially zinc (Zn), and several vitamins that are very good for health. Bioactive compounds that play a role in accelerating the wound healing process are albumin, glycine, and zinc (Zn). Wound healing is highly dependent on the biochemical processes that occur in the skin involving intrinsic and extrinsic factors. This healing process will be accelerated with the help of dried extracts of Snakehead fish designed in topical forms such as creams or gels